Stoic Cognitive Theories and Contemporary Neuropsychological Treatments - Kormas, Panagiotis (Conatus - Journal of Philosophy, 2022)
During the Hellenistic period the value of philosophical systems was to be judged by a meta-philosophical criterion, i.e., by their ability to lead practitioners towards the pursuit of good or happiness, albeit treating pain and sorrow, since all human beings are supposed to be able to reach the state of happiness via their own efforts. By emphasizing the role of thoughts or judgments, Stoics placed cognition in the intermediate phase between an event and the reaction that somebody has due to the event, rendering it both the cause and the cure of emotional disorders. This viewpoint is also fundamental in modern cognitive psychotherapy, although the parallelism goes beyond theory to the practical character in both approaches. Rational and non-rational aspects of human psychology cannot be isolated from each other, allowing thus adults to actively engage in their moral development by altering their beliefs. In this frame, cognitive distancing, the practice of awareness, attention to the present moment, and the Socratic dialogue become valuable tools in structuring emotional self-regulation.